Negeri Utama Bercorak SPiritual Madinah Fadhilah Ruhaniyah Perspektif Ikhwan Al-SHafa - Bahri, Media Zainul (Buletin Al-Turas, 2004)
A group of Moslem intellectual called Ikhwan Al Shafa is interested in philoshopy's problems. Through their greatÂ wark (magmum opus). Rasail Ikhwaan al-Shafa wa Khullan al-Wafa they expressed the new concept of country called MadinahÂ Fadilah Ruhaniyah. The county is full of nuance of peace, faimess, spirit and waltare.